2012
DOI: 10.1007/s00467-012-2169-x
|View full text |Cite
|
Sign up to set email alerts
|

Safety in glomerular numbers

Abstract: A low nephron number is, according to Brenner’s hyperfiltration hypothesis, associated with hypertension, glomerular damage and proteinuria, and starts a vicious cycle that ends in renal failure over the long term. Nephron endowment is set during foetal life, and there is no formation of nephrons after 34–36 weeks of gestation, indicating that many factors before that time-point may have an impact on kidney development and reduce nephron numbers. Such factors include maternal malnutrition, stress, diseases, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
1
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 52 publications
1
56
1
3
Order By: Relevance
“…An impaired GFR is a relatively late phenomenon in children with a solitary functioning kidney, because the first signs of renal injury generally include hypertension and (micro)albuminuria (5). Monitoring for renal injury in children with a solitary functioning kidney and a normal initial estimated GFR, therefore, should focus on BP and determination of (micro)albuminuria, which can both be done noninvasively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An impaired GFR is a relatively late phenomenon in children with a solitary functioning kidney, because the first signs of renal injury generally include hypertension and (micro)albuminuria (5). Monitoring for renal injury in children with a solitary functioning kidney and a normal initial estimated GFR, therefore, should focus on BP and determination of (micro)albuminuria, which can both be done noninvasively.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, nephrons are formed until the 34th to 36th gestational week, without the possibility of additional nephron formation later in life (5). This finding implies that the total of number of nephrons at birth, approximately 900,000 nephrons per kidney with a high interindividual variability (6), should last the entire lifespan of an individual.…”
Section: Causes Renal Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a plausible explanation as reduced nephron endowment has long been postulated to correlate with risk for hypertension as well as renal disease. 33 In contrast to the HSRA model, many studies using other models of congenital solitary kidney (rat 34 or pig 35 ) have observed compensatory nephrogenesis (i.e., increased nephron number). Similarly, studies in a novel sheep fetal nephrectomy model also demonstrated compensatory nephrogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that low birth weight or early life damage may have an impact on the kidney and its functions in later life [2,3]. It has already been shown that environmental influences during nephrogenesis, including growth restriction and medications, have a significant impact on final nephron numbers [4]. Nephrons are formed from the 5th gestational week onwards and formation ends around the 34th-36th week of gestation in humans [5].…”
Section: Introductionmentioning
confidence: 99%